Behavioural Insights Into Cybersecurity Practices Among Digital Banking Consumers in South Africa - Ntswaki Petunia Matlala (Indonesian Journal of Business Analytics, 2023)
Digital banking is linked with several cybersecurity threats, such as the risk of hackers. Against this background, this study aims to explore behavioural insights into cybersecurity practices among digital banking consumers in South Africa. The researcher gathered data from 338 South African banking consumers. A structured questionnaire was used to survey these consumers, and the obtained data were analysed using structural equation modelling (SEM). The results revealed that subjective norms, self-efficacy, and attitude significantly influence the cybersecurity intention behaviour of digital banking consumers. The implications of the study's findings need to be more readily generalisable due to the sociocultural differences across different provinces and populations. Future research should include a more diverse sample to validate these findings further.